2013
DOI: 10.1186/1477-5956-11-9
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring post mortem changes in porcine muscle through 2-D DIGE proteome analysis of Longissimus muscle exudate

Abstract: BackgroundMeat quality is a complex trait influenced by a range of factors with post mortem biochemical processes highly influential in defining ultimate quality. High resolution two-dimensional DIfference Gel Electrophoresis (2-D DIGE) and Western blot were applied to study the influence of post mortem meat ageing on the proteome of pork muscle. Exudate collected from the muscle following centrifugation was analysed at three timepoints representing a seven day meat ageing period.ResultsThe intensity of 136 sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 62 publications
0
34
0
1
Order By: Relevance
“…Di Luca et al (2013b) stated that muscle exudate could be a good source of these proteins because it provides valuable information about the pathways and processes underlying the post mortem ageing period as well as highlighting its post mortem modifications. Some studies have also shown that sarcoplasmic protein profile in drip loss is also determined by the feeding of animals (Shibata et al, 2009;Costa-Lima et al, 2015).…”
Section: Effect Of Lamb Diets On Drip Loss Protein Profilementioning
confidence: 99%
“…Di Luca et al (2013b) stated that muscle exudate could be a good source of these proteins because it provides valuable information about the pathways and processes underlying the post mortem ageing period as well as highlighting its post mortem modifications. Some studies have also shown that sarcoplasmic protein profile in drip loss is also determined by the feeding of animals (Shibata et al, 2009;Costa-Lima et al, 2015).…”
Section: Effect Of Lamb Diets On Drip Loss Protein Profilementioning
confidence: 99%
“…Rapid development of proteomics involves the application of various electrophoretic techniques [12,14,52,55], which allow the identification of many proteins with respect to their properties. It leads to better understanding of the causes and consequences of the phenomena influencing the quality of meat, especially its tenderness [15,20,22,31,32,35,40,47,51].…”
Section: Introductionmentioning
confidence: 99%
“…Although water-soluble sarcoplasmic proteins are not structural proteins in skeletal muscle, their post mortem proteolysis has been shown to occur in parallel with tenderization of meat (Bowker et al, 2008). Moreover, the water-soluble fraction contains fragments of myofibrillar proteins, which become extractable by post mortem proteolysis (Di Luca et al, 2013). Therefore, post mortem changes in water-soluble proteins are considered useful indicators of meat tenderness.…”
Section: Discussionmentioning
confidence: 99%